The development of grain growing in Omsk region in second half of 1960th and first half of the 1980th: trends, stages, results - D. S. Orlov (Омский научный вестник: Серия "Общество. История. Современность")
The reconstruction of the main stages of development of the grain industry in the Omsk region in 1960–1980s is carried out. It is established that the increase in the production of grain products at the time in question in the province alternated with periods of its fall. The dynamics of the grain industry was influenced by changes in the economic mechanism, the buildup of material and technical base, agrotechnology, and shifts in the structure of sown areas. At the same time, the main factor in the development of the industry remained weather and climate conditions, which had a decisive influence on fluctuations in the yield of grain crops